Pengetahuan dan Sikap Perilaku Hidup Bersih dan Sehat Siswa SDN 001 Buluh Cina Terhadap Tungau Debu Rumah - Lilly Haslinda; Andri Agustiandi (Fakultas Kedokteran Universitas Riau, 2021)
House dust mites (HDM) consists of a group of species of mites. Their size is very small and caused allergic reaction. A Parasitology house based survey conducted by Riau Provincial Health Office at SDN 001 Buluh Can at Kampar regency in 2014 found the high proportion of HDR (40,3%). The objective of this study was to find out the description of Clean and Healty Lifestyle (CAHL) knowledge and attitude of student of SDN 001 Buluh Cina, Kabupaten Kampar, Provinsi Riau. This study was a descriptive cross sectional with total number of are 97 respondents. This study showed that knowledge of CAHL toward HDM of 67 students are low (71,1%), 14 students (14,4%) are less and 14 studens(14,4%) are enough. Attitude of CAH Ltoward HDM of 54 student’s (55,7%) are negative and 43 students (44,3%) are positive. From this study concluded that the student’s knowledge of CAHL are low and the student’s attitude of CAHL toward HDM are negative.